Respuesta :

Answer:

Step-by-step explanation:

hg(x) means you multiply h(x) times g(x) and then we will set it equal to [tex]3x^2+x-1[/tex].

hg(x) = [tex]x^2(x+2)[/tex] which simplifies to

[tex]x^3+2x^2[/tex]. Now set that equal to [tex]3x^2+x-1[/tex]:

[tex]x^3+2x^2=3x^2+x-1[/tex] and get everything on the same side and factor:

[tex]x^3-x^2-x+1=0[/tex]. Factor by grouping:

[tex](x^3-x^2)-(x+1)=0[/tex] and factor out what's common in each set of ( ):

[tex]x^2(x-1)-1(x-1)=0[/tex] which factors out to

[tex](x^2-1)(x-1)=0[/tex]. But [tex]x^2-1[/tex] factors somoe to:

(x + 1)(x - 1)(x - 1) = 0 So the solutions for this are

x = -1, 1

ACCESS MORE